2012
DOI: 10.1186/2251-712x-8-20
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting time and place of earthquakes using a Semi-Markov model (with case study in Tehran province)

Abstract: The paper examines the application of semi-Markov models to the phenomenon of earthquakes in Tehran province. Generally, earthquakes are not independent of each other, and time and place of earthquakes are related to previous earthquakes; moreover, the time between earthquakes affects the pattern of their occurrence; thus, this occurrence can be likened to semi-Markov models. In our work, we divided the province of Tehran into six regions and grouped the earthquakes regarding their magnitude into three classes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…A more structured approach is attempted by Sadeghian (2012), who applied a statistical clustering algorithm to magnitudes, and again by Votsi et al (2012) when they propose a different classification of states that combines both magnitude and fault orientation information. From a modelling viewpoint, this latter approach is certainly preferable, because it is likely to produce more homogeneous classes, however we do not have enough additional information to attempt this type of classification of our data in a meaningful way.…”
Section: A Test Datasetmentioning
confidence: 99%
“…A more structured approach is attempted by Sadeghian (2012), who applied a statistical clustering algorithm to magnitudes, and again by Votsi et al (2012) when they propose a different classification of states that combines both magnitude and fault orientation information. From a modelling viewpoint, this latter approach is certainly preferable, because it is likely to produce more homogeneous classes, however we do not have enough additional information to attempt this type of classification of our data in a meaningful way.…”
Section: A Test Datasetmentioning
confidence: 99%
“…According to the model, the magnitude of an earthquake depends on the magnitude of the previous earthquake and the time interval between them. This may indicate that a long period seismic quiescence may end with an earthquake of large magnitude [6,7,8,33].…”
Section: Introductionmentioning
confidence: 99%
“…The forecasting ability of the semi-Markov model was also tested (Sadeghian, 2012) A continuous-time semi-Markov model has been applied to a dataset of earthquakes with M ≥ 5.5 that occurred from 1953 to 2007 in the region of the Northern Aegean Sea, which accommodates high seismic activity (Votsi et al, 2012). Earthquake occurrence rates were evaluated and it was found that the probability of an earthquake occurrence for a given state j (the states refer to the magnitude) increases as time elapses.…”
Section: Introductionmentioning
confidence: 99%